Impact of Predation by Ciliate Tetrahymena borealis on Conjugation in Aeromonas salmonicida subsp. salmonicida - Alicia F. Durocher; Valérie E. Paquet; Rébecca E. St-Laurent; Caroline Duchaine; Steve J. Charette (MDPI AG, 2024)
Background/Objectives: Antibiotic resistance gene (ARG) spread is driven by horizontal gene transfer (HGT). Ciliated protozoa may contribute to this process, as their predation has been shown to facilitate HGT in certain bacteria. Here, this phenomenon was further investigated using A. salmonicida subsp. salmonicida. This fish pathogen bears an extensive and dynamic plasmidome, suggesting a high potential for HGT. Methods: A. salmonicida strains carrying one of three conjugative plasmids bearing ARGs (pSN254b, pRAS1b or pAsa4b) were cocultured with a recipient, either A. salmonicida, E. coli or A. hydrophila. Conjugation rates were assessed in the presence and absence of the ciliate Tetrahymena borealis. PCR genotyping confirmed the acquisition of the conjugative plasmids and was used to verify the mobilization of other plasmids. Results: The basal rate of conjugation observed was high. Under the conditions studied, ciliate predation did not appear to influence the conjugation rate, except at higher proportions of ciliates, which typically hampered conjugation. Microscopy revealed that most bacteria were digested in these conditions. PCR screening demonstrated that small mobilizable plasmids from A. salmonicida (pAsa1, pAsa2, pAsa3, and pAsal1) were acquired by the recipients along with the conjugative plasmids, with a slight effect of the ciliates in some donor/recipient cell combination. Conclusions: These results highlight how A. salmonicida can conjugate efficiently with different species and how complex its relationship with ciliates is.